2005
DOI: 10.3354/dao063215
|View full text |Cite
|
Sign up to set email alerts
|

Myxidium mackiei (Myxosporea) in Indo-Gangetic flap-shelled turtles Lissemys punctata andersonii: parasite-host interaction and ultrastructure

Abstract: Myxosporeans are common parasites of fish, and uncommon parasites of amphibians, reptiles and invertebrates, that can cause significant morbidity and mortality. The common genus Myxidium infects the excretory system of turtles, yet knowledge of its pathogenicity in these hosts is limited. We offer new knowledge of morphological and ultrastructural aspects of host -parasite interactions in Myxidium infections from our recent diagnostic investigations on captive freshwater turtles listed in CITES (Appendix II). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…This myxozoan was seen in renal tubules of 3 turtles, the gall bladder of 2 turtles and bile ductules of 1 turtle. Similarly M. americanum, M. hardella, and M. mackiei also infect both urinary and biliary tracts, while M. chelonarum has been primarily identified from the gall bladder (Johnson 1969, Garner et al 2005, Helke & Poynton 2005.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This myxozoan was seen in renal tubules of 3 turtles, the gall bladder of 2 turtles and bile ductules of 1 turtle. Similarly M. americanum, M. hardella, and M. mackiei also infect both urinary and biliary tracts, while M. chelonarum has been primarily identified from the gall bladder (Johnson 1969, Garner et al 2005, Helke & Poynton 2005.…”
Section: Discussionmentioning
confidence: 99%
“…M. immersum and M. serotinum from amphibians also appear to lack host specificity (Eiras 2005) and may represent multiple species. DNA sequencing will be needed to determine the phylogenetic relationship of these myxozoan parasites.Recent studies have shown congruency in spore valve morphology from Asian and American species of Myxidium (Helke & Poynton 2005). Phylogenetically, M. hardella and M. chelonarum, both from Asian turtles, formed a well-supported grouping.…”
mentioning
confidence: 98%
See 3 more Smart Citations